Hubungan Beban Kerja Fisik Dengan Keluhan Nyeri Punggung Bawah Pada Physiotherapist Di Rumah Sakit Wilayah Jawa Timur - Andy Setyawan; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective : To identify the association of workload physical with low back pain complaints in worker in hospital of the East Java Region. Methods : This article were descriptive correlational type with data collection techniques carried out by questionnaires. Collecting respondent data by sending a questionnaire with the technique of sending a google form with a link is https://forms.gle/E4UwRxAoLTBcbEL69 to all physiotherapists in East Java region, then from the results of respondents who sent data there were 166 physiotherapists. Then  the  data is reduced which is in accordance with the criteria, namely respondents who work in hospitals and who have experienced low back pain. From these data, the researcher can present it and conclude. Results : The result showed that the physiotherapist's age range is 24-56 year old. The results of research on physiotherapists who work in hospital type A, B and C in East Java region who have sent data are 88,2% of physiotherapists who experience low back pain complaints, for those who experience a minimum of disability are 79,9%, mild is 17,2%, moderate 2,2% and 0,7% for severe paralysed.Conclusion : The workload physical of physiotherapists has a significant relationship with complaints of perceived low back pain. In other words, the heavier the workload physical will increase the severity of low back pain complaints felt by the physiotherapist.